2023
DOI: 10.5539/jsd.v16n3p89
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Climate Smart Agricultural Technologies among Smallholder Farmers in Semi-Arid Ghana

Abstract: The evidence of climate change and variability in semi-arid Ghana is glaring and the adverse impact is being felt mostly by smallholder farmers because of their over dependence on agriculture for livelihood and subsistence. As a solution to building the resilience of the smallholder farmers, the Climate Smart Agriculture (CSA) concept was introduced a decade ago by the Food and Agriculture Organization, guided by three key principles of adaptation to climate change, greenhouse gas emissions reduction and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Almost same order of importance of the problems was reported in a study conducted for examining the problems faced by farmers in adoption of improved technologies [6]. A study in Ghana among small farm holders showed similar result [9]. The financial constraints like lack of required finance and high cost of inputs comes out as major limitations in adaptation of crop-livestock integrated system at Madhya Pradesh [10].…”
Section: Resultsmentioning
confidence: 53%
“…Almost same order of importance of the problems was reported in a study conducted for examining the problems faced by farmers in adoption of improved technologies [6]. A study in Ghana among small farm holders showed similar result [9]. The financial constraints like lack of required finance and high cost of inputs comes out as major limitations in adaptation of crop-livestock integrated system at Madhya Pradesh [10].…”
Section: Resultsmentioning
confidence: 53%